PENERAPAN PROJECT BASED LEARNING BERBASIS KEARIFAN LOKAL TRI HITA KARANA MENINGKATKAN SIKAP GOTONG ROYONG - Monika, Ketut Ayu Lola; Suastika, I Nengah; Sanjaya, Dewa Bagus (Dharmas Education Journal (DE_Journal), 2023)
Elementary school students lack the ability to apply learned models that foster mutual cooperation and instill local wisdom, making them less able to work together and collaborate with friends. As a result, Tri Hita Karana-Based Learning Project classroom action research was carried out with the intention of improving students' attitudes toward democracy. This action research in the classroom was conducted in fourth grade. This classroom action research employs descriptive qualitative analysis to examine learning activity processes as data. The mutual cooperation attitude score is analyzed using quantitative descriptive analysis. Instrument for collecting data with a democratic attitude survey. The results of class action research show that in the first cycle, the average attitude of mutual cooperation was 68.7, with a median of 70 and a mode of 70. In the second cycle, the average attitude of mutual cooperation increased to 86, with a median of 85 and a mode of 85. As a result, the application of the Tri Hita Karana-based Project Based Learning model may have resulted in an increase in elementary school students' attitudes toward mutual cooperation.